Three knots to nowhere : a Cold War submariner on the undersea frontline - Dubay, Ted E. (McFarland & Company, Inc., Publishers, 2014)
"This work follows the author's experiences in the United States Navy, 1966-1972, including a personal background, boot camp, electricians school, the U.S. Naval Nuclear Program, assignments to the ballistic missile submarine USS Henry Clay, subsequent transit to Hawaii, and deterrent patrols out of Guam. This narrative focuses on the enlisted men--the backbone of the submarine service"--